Enantioselective intermolecular iodoacetalization of enol ethers catalyzed by chiral Co(III)-complex-templated Brønsted acids. Issue 40 (3rd October 2018) - Li, Na; Yu, Hao; Wang, Rui; Shen, Jia; Wu, Wen-Qiang; Liu, Kun; Sun, Ting-Ting; Zhang, Zheng-Zhu; Yao, Chuan-Zhi; Yu, Jie
Graphical abstract: Highlights: Employing chiral Co(III)-complex-templated Brønsted acids as catalysts. The asymmetric intermolecular iodoacetalization of enol ethers was achieved. This method provided an easy access to optically active 3-iodoacetal derivatives. High yield and up to 83:17 er. Abstract: The chiral Co(III)-complex-templated Brønsted acids were used as efficient bifunctional phase-transfer catalysts for the asymmetric intermolecular iodoacetalization of enol ethers, such as 3, 4-dihydro-2H-pyran, 2, 3-dihydrofuran, ethyl vinyl ether with alcohols and NIS, furnishing the 3-iodoacetals in high yield with up to 83:17 er.